Sistem Pendukung Keputusan Penentuan Jurusan SMA N 2 Sukoharjo Dengan Menggunakan Metode Fuzzy - Satiti, Dyah; , Yogiek Indra Kurniawan, S.T., M.T (2017)
In the appointment of the department is one of the process of channeling in the selection of teaching programs to students in high school level. Therefore a decision support system is needed to assist in the determination of the department. In this research the determination of the majors in SMA N 2 Sukoharjo required selection to determine the majors of the majors of MIPA, IPS or BB. This study aims to implement fuzzy mamdani method into decision support system. The fuzzy mamdani method is used to model information containing fuzzy numbers, and fuzzy can also process these numbers using ordinary arithmetic numbers so as to produce real sums at intervals, this study uses inputs and outputs for the process of determining majors. The input variables used in this fuzzy calculation are the value of interest, the average value of SMP and the value of talent, while the output variable is MIPA, IPS or BB. The final result of this research is the decision support system of determination of SMA N 2 Sukoharjo based on predetermined criteria, this system produce the final result of accuracy of data testing with percentage 89,6%.